Onco: A Promising Player Amidst Oncology Journals - Constantin N. Baxevanis (Onco, 2023)
As the new Editor-in-Chief of the journal, I believe that I must continue the efforts of my predecessor even more actively and with greater enthusiasm and dedication so that the journal becomes a pole of attraction for the publication of excellent studies of basic, translational and clinical research for the treatment of cancer [...]